MENEJEMEN NYERI - Gunadi, Eka; Istiana, Trismi (CV. Jasa Sukses Abadi, 2024)
Pain is the most common chief complaint for emergency derpatment admission. Pain is sensory and emotional experience, unpleasant one, which may be related to threat of or process of tissue damage which is made by neuronal signalling. Globally, almost everone experiences pain in a year and one-third of world population experience chronic pain. Etiology of pain itself is various and its impacts negatively affect one’s activities of daily living (ADL) and quality of life (QoL), as well as their socioeconomics. World Health Organization (WHO) has created a guideline for pain management. This guideline suggests non-opioid, weak opioid, and strong opioid for analgesic depends on pain severity. Additional antidepressant, anticonvulsion, corticosteroid, or anxiolytic drug can also be givent for better analgesic outcome. What class drug to choose has to be based on one’s subjective pain experience, with fitted dose, and strict observation on possible side effects from chosen drugs. This guidance, unfortunatey, sometimes isn’t applied practically in managing pain, which makes the therapy less effective and efficient, causes increase in adverse events, as well as increase the risk of opioid dependence. The purpose of this article writing is to review pain management, hence its application in practice may be beneficial for many people.